Answer:
x = 3 ±sqrt(6)
Step-by-step explanation:
6(x-3)^2-26 = 10
Add 26 to each side
6(x-3)^2-26+26 = 10+26
6(x-3)^2 = 36
Divide by 6
6/6(x-3)^2 = 36/6
(x-3)^2 = 6
Take the square root of each side
sqrt((x-3)^2) = ±sqrt(6)
x-3 = ±sqrt(6)
Add 3 to each side
x-3+3 =3 ±sqrt(6)
x = 3 ±sqrt(6)
That's 4! (faculty), ie., 4x3x2x1 = 24.
one of four can win, then there are 3 left for second place, and so on...
Answer:
same moon
Step-by-step explanation:
Answer:
80
Step-by-step explanation:
Answer:
16 0z/1 ib
Step-by-step explanation:
it is not a quantity over time